On the Effectiveness of Central Bank Intervention in the Foreign Exchange Market: The Case of Slovakia, 1999–2007. Issue 3 (September 2018) - Banerjee, Biswajit; Zeman, Juraj; Ódor, Ľudovít; Riiska, William
Abstract Based on intraday high-frequency data, this paper investigates the effect of sterilized interventions on the Slovak koruna/euro exchange rate for different time windows during a period that coincides with Slovakia's preparation for EU accession and euro adoption. Results confirm a significant relationship between intervention and exchange rate change. The maximum effect of intervention is reflected in the exchange rate change within a couple of hours, and the effect over longer time windows weakens only gradually. The initial impact of sale interventions is stronger than that of purchase interventions.